The Structure of Interest Rates - Lutz, F. A. (Quarterly Journal of Economics, 1940)
I. Assumptions, 36. — Five propositions concerning the relationship between short and long rates, 37. — II. Influence of the costs of investment, 41. — Shiftability on the lenders' side, 43. — Two complications: many maturities, 44; the function of banks as changers of maturities, 45. — III. The influence of risk, 46. — IV. Expectations: the rational investor's decisions, 48; possible inconsistencies, 49. Effect of divergent expectations among members of the market, when the majority expect rising interest rates, 51; when "the market" expects rates to fall, 54. — V. Verification: movement of interest rates over time, 55; structure of yields on different maturities, 56. — VI. Bearing of this analysis on: influence of the discount rate on investment, 60; interest and the marginal efficiency of capital, 60; influence of wide gaps between short and long rates, 61; the "liquidity theory of interest, " 62.